Fetal programming: could intrauterin life affect health status in adulthood? - Hande Nur Onur Öztürk; Perim Fatma Türker (Korean Society of Obstetrics and Gynecology, 2021)
Intrauterine life is one of the most important periods of life. As the development of the fetus continues, the mechanisms that affect adult health also begin to mature. With the hypothesis denoted "fetal programming," it is thought that the presence of endocrinological disorders, toxins, infectious agents, the nutritional status of a mother, and nutrients related to placental functionality all have an effect on future life. Therefore, the fetus must adapt to the environment for survival. These adaptations may be involved the redistribution of metabolic, hormonal, or cardiac outputs in an effort to protect the brain, which is one of the important organs, as well as the slowing of growth to meet nutritional requirements. Unlike lifestyle changes or treatments received in adult life, the early developmental period tends to have a lasting effect on the structure and functionality of the body. In this review, fetal programming and the effects of fetal programming are discussed.